1993
DOI: 10.1128/aac.37.6.1318
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of drug susceptibility in Plasmodium falciparum in vitro and Plasmodium berghei in vivo by mixed-function oxidase inhibitors

Abstract: A number of compounds, as exemplified by verapamil and desipramine, have been shown to enhance the susceptibility of resistant malaria parasites to chloroquine. The mechanism by which these agents reverse resistance is still controversial but is thought to involve alterations in drug transport causing an increase in steady-state drug concentrations. We have proposed that an alternative resistance mechanism may involve the metabolic deactivation of the drug in some resistant parasites via cytochrome P-450 mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
(20 reference statements)
1
8
0
1
Order By: Relevance
“…This observation is unique and unexpected considering that the drug-selected parasite lines had lost the VP-sensitive CQR phenotype on selection for resistance to amantadine and halofantrine, respectively (14). The observation that pretreatment with PB results in an increased resistance to CQ confirms the observations made by Ndifor et al (21,22). The effect of PB on the growth rate of the parasite lines was determined by microscopic analysis.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This observation is unique and unexpected considering that the drug-selected parasite lines had lost the VP-sensitive CQR phenotype on selection for resistance to amantadine and halofantrine, respectively (14). The observation that pretreatment with PB results in an increased resistance to CQ confirms the observations made by Ndifor et al (21,22). The effect of PB on the growth rate of the parasite lines was determined by microscopic analysis.…”
Section: Resultssupporting
confidence: 75%
“…It is well known that PB induces the expression of CYPs and ABC transporter proteins in mammals via nuclear receptor-dependent mechanisms (10, 11, 13, 16, 34-36, 42, 48). The changes in CQ susceptibility observed after PB treatment could feasibly be controlled by an increased metabolism of CQ by CYPs, a hypothesis originally put forward by Ndifor et al (21,22). However, it has been shown that CQ is not metabolized by malarial parasites (29,43).…”
Section: Discussionmentioning
confidence: 90%
“…These preliminary data suggest that chloroquine deactivation may be partly responsible for the observed drug resistance. [138] 8. Stereoselective Pharmacokinetics and Pharmacodynamics…”
Section: Chloroquine Resistancementioning
confidence: 99%
“…In the CQ (4 mg/kg dose)-treated group, a slight prolongation of survival time was observed compared with control, as all the mice in this group died by day 11 postin¬ fection. In contrast, in the group of mice treated with a low dose of Poly ICLC (1.77 mg/kg dose) in combination with CQ (4 mg/kg dose), the initial onset of patent parasitemia was slowed, followed by a gradual increase in parasitemia, reaching a max¬ imum of 20%-25% on day [12][13][14][15][16][17][18] fNw nitro-L-arginine 13.2 mg/kg/day for 6 days.…”
Section: Resultsmentioning
confidence: 67%